Substrate Anchoring and the Catalytic Power of Enzymes - Reuben, Jacques (1971)
Evidence from published nuclear magnetic resonance studies of enzyme-substrate and enzyme-inhibitor systems systems shows that substrates are confined at the active site of the enzyme, have a relatively long residence time, and tumble in solution as an enzyme-substrate complex. The consequences of this “substrate anchoring” with regard to the catalytic power of enzymes are considered. It appears that as a result of the relatively slow motions, the probability of existence of the “activated complex” in the enzymatic reaction may be increased and thus the reaction rate may be accelerated by factors of between 10(6) and 10(9). It is estimated that the combined effect of substrate anchoring, desolvation, and charge compensation may lead to reaction-rate accelerations by factors of between 10(9) and 10(8).